The film industry in Zimbabwe- growth and production challenges: a case of Gona raMachingura and Checkmate - Garatsa, Christopher (Midlands State University, 2019)
This research scrutinised the film services sector and the value chain in film production in Zimbabwe. This was in a bid to assess the practices and divulge challenges that are faced by film players and the way these hinder growth of the sector. The research used case studies of two films, Checkmate and Gona raMachingura as it was impossible to look at the sector in its entirety. Qualitative methods were employed in the research. The findings from the two cases complimented each other and were analysed in themes. There was a disorganisation and high level of unprofessionalism in the production of these two films. These findings, were concluded, are reflective of the generality of the industry and have a hindering effect on the growth prospects of the industry as a whole.